ALTRUISME PADA PEMBUAT SHELTER: PERAN DALAM PENYELAMATAN HEWAN TERLANTAR - Jose Conary; Untung Subroto; Meike Kurniawati (STKIP Subang, 2024)
This study aims to understand the picture of altruism in individuals who set up shelters for abandoned animal rescue in Indonesia. Altruism in this context is characterized by selfless actions driven by deep empathy for the suffering of abandoned animals. Using a qualitative approach, data was collected through in- depth interviews and observations of four participants who were aged 20-60 years old and had managed a shelter for at least six months. The results showed that the participants' motivation was driven by various factors, such as high empathy, pure intention, internal motivation, and prioritization of others' welfare. The forms of altruism demonstrated include rescuing animals from dangerous environments, providing safe shelter, medical care for injured or sick animals, and educating the public to raise awareness about animal welfare. However, participants face various challenges, including limited funding, lack of community support, lack of human resources, and emotional distress from seeing the constant suffering of animals. Despite this, their dedication remains high, demonstrating an ongoing commitment to making a positive impact on abandoned animals. This research confirms that altruism plays an important role in creating positive social change, not only to improve animal welfare but also to inspire people about the importance of caring for living beings. This study contributes to the understanding of altruistic actions in the unique context of abandoned animal rescue in Indonesia.